Dysthanasia in the Ecuadorian constitutional State as a formula for the treatment of catastrophic diseases - Álava Bravo, Darwin Ariel (2024)
Life is a legal asset of special protection, in such a way that anything that violates this right must be subject to sanction. Thus, the protection, preservation and prolongation of life is the axiomatic axis that crystallizes the rights of “Good Living.” The research aims to determine the protection of the practice of distance as a formula for the treatment of catastrophic diseases in the face of the recognition of the right to a dignified life in the constitutional State. This legal-doctrinal research was developed under a qualitative approach, systematizing the bibliographical collection compiled through the problem tree technique and the use of the exegetical method. The results allow us to recognize that life is a legal good of superlative value; however, life and death are two aspects that come together under the constitutional desideratum of the rights of “Good Living.” For this reason, its protection must be balanced with practices that maximize its preservation to the extent that it is humanly necessary. It is concluded that the State must assume scientific, rational and moral criteria that guide public policy decisions on this matter without affecting the value of human dignity.